Youth at Risk or Terms at Risk?. (August 2015) - Follesø, Reidun
In this article, I ask how the two terms youth and risk are connected to each other. What are the predominant descriptions for this collective term, and what consequences can such descriptions lead to? In conclusion, I ask if there may be alternative terms that could be used to encourage understanding and active movement in other directions. My hope is to challenge predominant understandings of 'youth at risk'. To achieve this, we must ask new questions and search for alternative terms. In order to succeed, we need to include those who are affected by the terminology—those who have to wear the label. In so doing, we may search for and find terms that that are open, inclusive and make it possible to take positive new actions.